Influence of dental plaque pH on caries status and salivary microflora in children following comprehensive dental care under general anesthesia - Yng-Tzer J. Lin; Yai-Tin Lin (Elsevier, 2018)
Background/purpose: There is no report in examining dental plaque pH after dental care under general anesthesia. This study investigated the effects of comprehensive dental rehabilitation under general anesthesia on the oral environment of children with severe early childhood caries (S-ECC) and the influence of dental plaque pH on caries recurrence and salivary microflora. Materials and methods: Thirty-seven children (mean age, 51.08 ± 9.68 months) with S-ECC who underwent comprehensive dental treatment under general anesthesia were selected. Caries index, plaque pH, and Streptococcus mutans (SM) and Lactobacillus (LB) counts were evaluated during the initial examination and 6-month and 12-month follow-ups. Results: The plaque pH was significantly greater at the 6-month follow-up examination than at the initial examination (P = 0.006) and at the 12-month follow-up (P = 0.002), but there was no significant difference in plaque pH between the initial examination and the 12-month follow-up (P = 0.942). SM and LB counts at the sixth and twelfth months were significantly lower than the initial counts (P < 0.001). Plaque pH did not show strong correlations with caries index and SM and LB counts at the three time-points (P > 0.05). Conclusion: The comprehensive dental rehabilitation under general anesthesia for children with S-ECC caused a temporary significant increase in the plaque pH at the sixth month and a significant reduction in the salivary microflora during the 12-month follow-up. Plaque pH did not demonstrate any strong correlations with caries status and salivary microflora in children with S-ECC. Keywords: caries status, plaque pH, salivary microflora